2018
DOI: 10.1007/s00592-018-1161-8
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer-derived physical activity in those with cardio-metabolic disease compared to healthy adults: a UK Biobank study of 52,556 participants

Abstract: AimCardio-metabolic disease and physical activity are closely related but large-scale objective studies which measure physical activity are lacking. Using the largest accelerometer cohort to date, we aimed to investigate whether there is an association between disease status and accelerometer variables after a 5-year follow-up.Methods106,053 UK Biobank participants wore a wrist-worn GENEactiv monitor. Those with acceptable wear time (> 3 days) were split into 4 cardio-metabolic disease groups based on self-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 4 publications
2
30
3
Order By: Relevance
“…Analyses were completed in SPSS (version 25), except for confirmatory and exploratory factor analyses, which were completed in MPlus 7.3. Participants’ outcome data were analysed descriptively and compared to population norms to determine whether scores differed significantly to comparable samples’ scores on wellbeing [10], depression, anxiety, and stress [30], quality of life [31], subjective physical activity [32], objective physical activity [33], and sleep duration [34].…”
Section: Discussionmentioning
confidence: 99%
“…Analyses were completed in SPSS (version 25), except for confirmatory and exploratory factor analyses, which were completed in MPlus 7.3. Participants’ outcome data were analysed descriptively and compared to population norms to determine whether scores differed significantly to comparable samples’ scores on wellbeing [10], depression, anxiety, and stress [30], quality of life [31], subjective physical activity [32], objective physical activity [33], and sleep duration [34].…”
Section: Discussionmentioning
confidence: 99%
“…Results from the Whitehall II study showed 1) the association between physical activity and body mass index was much stronger when using accelerometer data rather than questionnaire data (Sabia et al, 2015); 2) obese people with an unfavorable metabolic profile had a lower level of physical activity than those with a healthy metabolic profile, which was not evident when using questionnaire data (Bell et al, 2015); 3) the association between moderate and vigorous physical activity and healthy aging was evident whether the activity was performed in short (<10 minutes) or long (≥10 minutes) bouts (Menai et al, 2017). Results from the UK Biobank also showed 1) people with cardiometabolic disease are less physically active and tend to engage more in sedentary activities that last more than 30 minutes (Cassidy et al, 2018), and 2) short bursts of very high intensity physical activity are associated with better bone health in pre-and postmenopausal women (Stiles, Metcalf, Knapp, & Rowlands, 2017).…”
mentioning
confidence: 99%
“…Recently, Rowlands et al 58 reported average MVPA durations of 92 min/day for a small adult sample, using the GeneActiv. A recent study using the large (n=22 978) Biobank dataset reported 106 min/day MVPA in healthy adults 59. In children, Telford et al 60 reported averages of 43 and 31 min/day of MVPA for boys and girls aged 8–12 years, respectively.…”
Section: Discussionmentioning
confidence: 99%